Education of Children with Disabilities in India: A Case Study: Policies, challenges, and recommendations for educating children with disabilities in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Education is the right of every child because it equips him to meet the challenges of life. The children with disabilities (CWD) need this all the more, to supplement their differential talents so that they can prepare themselves for a happy productive and useful life. Efforts to educate children with disabilities began soon after independence in India. An attempt has been made to examine the policies and legislations for educating the children with disabilities in India after post- constitution era. In the final section, challenges for providing education to CWD and in that light some recommendations were made. In India, different definitions of disability conditions have been introduced for various purposes, essentially following the medical model and, as such, they have based on various criteria of ascertaining abnormality or pathologic conditions of persons.